Velamentous cord insertion: a rare cause of emergency caesarean section - Raimi Z; Ng, Beng Kwang; Abdul Kadir AK; Lim, Pei Shan (Faculty of Medicine, Universiti Kebangsaan Malaysia Medical Centre, 2016)
Pregnancies complicated with velamentous cord insertion (VCI) are at risk of adverse perinatal outcome. Placental and umbilical cord assessment should be performed during routine obstetric ultrasound. We report a case of velamentous cord insertion that was not identified antenatally. A 28-year-old primigravida at 40 weeks gestation presented in active phase of labour. Intrapartum, cardiotocography (CTG) tracing was pathological. Thus, decision was made for emergency caesarean section and a velamentous cord insertion was found. Despite a favourable outcome, this case highlighted the importance of antenatal diagnosis of VCI and thus preventing catastrophic outcome.